If I Were a Dictator - Reynolds, Quentin James (Tufts Archival Research Center, 2006)
Quentin Reynolds explains why he would first burn the Bible if he were a dictator: the Bible is the source of democracy and its stories tell of the power of individuality and non-conformity which make a dictatorship impossible, according to Reynolds.